Baltic blue mussel (Mytilus edulis L.) and black soldier fly (Hermetia. illucens) combined with pea protein concentrate as protein sources in feed for rainbow trout (Oncorhynchus mykiss) - Cui, Xiaoqing (SLU/Dept. of Animal Nutrition and Management (until 231231), 2019)
A feeding trial was conducted for 9 weeks to test the growth performance, nutrient retention and digestibility in rainbow trout (Oncorhynchus mykiss) in order to assess the potential of Baltic blue mussel meal (Mytilus edulis L) and black solider fly larvae (Hermetia illucens) meal as protein sources. The dietary treatments consisted of one control diet based on high quality fishmeal, one control diet based on pea protein concentrate for testing dietary palatability and two fishmeal-free experimental diets where approximately 20% of the crude protein from the fishmeal was replaced with the protein from either de-shelled blue mussel meal or larvae meal on a dry matter basis. These four experimental diets were randomly fed to quadruplicate groups of fish. Replacing the dietary fishmeal with mussel meal and larvae meal negatively affected feed intake, final body weight, specific growth rate, feed conversion ratio and nutrient retention of rainbow trout. The apparent digestibility coefficient (ADC) of crude protein, crude lipid, and essential amino acids was not affected by replacing the dietary fishmeal with mussel meal and fish fed mussel meal diet even displayed increased nutrients digestibility, compared with fish fed control diet. Replacing fishmeal with larvae meal did not affect the apparent digestibility coefficient of crude protein. In conclusion, the ADC values showed that both mussel meal and larvae meal could be regarded as promising protein sources for rainbow trout. However, the growth performance and nutrient retention were negatively affected by low feed intake. The absence of fishmeal and the high inclusion of pea protein concentrate in the diets resulted in the poor palatability and were considered the reasons of low feed intake. Therefore, inclusion of fishmeal or feed stimulants might be needed to increase feed palatability. Furthermore, the inclusion of pea protein should be adjusted to an appropriate level.